Excessive manganese content in children’s multivitamin supplements: Potential for neurodevelopmental harm and other adverse health outcomes - Seth H. Frisbie; Erika J. Mitchell; Amy Hoeltge; Lindsey A. Pett; Molly G. Hoeltge (PLoS ONE, 2026)
Background Manganese (Mn) is an essential nutrient vital for many physiological processes, but it can cause adverse health effects at high exposures, particularly during neurodevelopment. Mn is included in many children’s multivitamins and mineral supplements, but it has not been documented whether the levels of Mn in such supplements are appropriate or safe. In this study, we measured Mn concentrations in children’s multivitamin and mineral supplements and compared the concentrations to the Institute of Medicine’s (IOM’s) tolerable Upper intake Levels (ULs). Methods We purchased 52 multivitamin and mineral supplements in various forms, including tablets, capsules, gummies, powders, and liquids. Of these samples, half listed supplemental Mn on their labels; half did not. We quantified their manganese concentrations using inductively coupled plasma-optical emission spectroscopy. We compared the measured Mn concentrations of the samples to the labeled concentrations and to the IOM ULs. Results Of the 26 products with supplemental Mn on their labels, 23 (88.5%) contained more Mn than shown on the label, while 3 (11.5%) contained less. The mean percent difference between labeled and measured Mn content was 42.5%. One product (4%), a liquid, would exceed the IOM’s Mn ULs based on labeled concentrations alone if consumed daily, 5 products (19%) would exceed IOM ULs based on measured concentrations, and 9 (34.6%) would exceed IOM ULs based on measured concentrations if used as supplements to ordinary diets. Of the 26 products without supplemental Mn listed on their labels, 13 (50.0%) contained measurable Mn concentrations. None of the products without supplemental Mn listed on their labels would exceed IOM ULs, even if consumed as supplements to ordinary diets. Conclusions Some children’s multivitamin supplements may lead to exceedances of IOM ULs for Mn, especially when consumed as supplements to ordinary diets.